"Unfortunately I'm a Massively Heavy Sleeper": An Analysis of Fathers' Constructions of Parenting. (August 2020) - Borgkvist, Ashlee; Eliott, Jaklin; Crabb, Shona; Moore, Vivienne
Expectations for fathers have changed over the past few decades—research has shown that many men express more egalitarian views toward fatherhood and being more involved in parenting, particularly in the caretaking and emotional aspects of parenting. However, despite intentions expressed before parenthood, parenting will often play out along more traditional, gendered lines. In this research, we demonstrate how discourses used by fathers might work to maintain gendered divisions in relation to parenting and work. Data were collected through semistructured interviews that covered men's experiences of work and parenting. Discourse analysis was employed to analyze the data. We identified that while participants expressed a desire to be involved fathers, often this did not transpire. Participants' inability to, or decisions not to be, actively involved was accounted for in various ways, and suggested a tension between what fathers recognize they should be doing, and what they are doing, as parents.